Serum levels of lipid and lipoproteins in patients with beta- thalassemia in Amara S.Iraq - A. M., Mohammed (University of Thi-Qar Journal of Science, 2009)
Lipid profile was estimated in sera of patients in major thalassemia (Tmajor),minor thalassemia (Tminor) compared with control group. 95 individual (26minor),(29major) was admitted to thalassemic center in Amara city .S.Iraq ,and 40 healthy as control group. Lipid profile which include Cholesterol (Ch),Triglyceride(TG),Phospholipid (Ph.L),Total lipid (T.L),High density lipoprotein -Cholesterol (HDL-C),Low density lipoprotein-Cholesterol (LDL-C),Very low density lipoprotein-Cholesterol (VLDL-C) .In our study there were found increase levels of Ch,TG,HDL-C,VLDL-C and total lipid in sera of both patient groups compared with control,while alower of LDL-C and Ph.L levels was found in sera of minor and major thalassemia patients.